Unusual Clinical Presentation of Ethylene Glycol Poisoning: Unilateral Facial Nerve Paralysis. (3rd November 2013) - Eroglu, Eray; Kocyigit, Ismail; Bahcebasi, Sami; Unal, Aydin; Sipahioglu, Murat Hayri; Kocyigit, Merva; Tokgoz, Bulent; Oymak, Oktay
Abstract : Ethylene glycol (EG) may be consumed accidentally or intentionally, usually in the form of antifreeze products or as an ethanol substitute. EG is metabolized to toxic metabolites. These metabolites cause metabolic acidosis with increased anion gap, renal failure, oxaluria, damage to the central nervous system and cranial nerves, and cardiovascular instability. Early initiation of treatment can reduce the mortality and morbidity but different clinical presentations can cause delayed diagnosis and poor prognosis. Herein, we report a case with the atypical presentation of facial paralysis, hematuria, and kidney failure due to EG poisoning which progressed to end stage renal failure and permanent right peripheral facial nerve palsy.